The synthesis of epoxy monomers with mesogenic groups - Mossety-Leszczak, B.; Wojciechowski, P.; Galina, H.; Ulański, J. (Polimery, 2022)
A two-step synthesis was developed to prepare new types of diepoxy and diolefinic liquid crystalline (LC) monomers. The synthesis involved (i) esterification of 4-hydroxyphenyl-4-hydroxybenzoate or 4’,4’-biphenol (I) with 4-pentenoic acid (II); (ii) epoxidation of the resulting diolefins with m-chloroperoxybenzoic acid. The structure of the resulting products was confirmed in terms of FTIR and ]H NMR spectra. A hot-stage polarizing microscope showed mesophases to occur in the monomers 2b, 3a and 3b (cf. scheme of reaction 1), but not in the product of esterification of I with II. Differential scanning calorimetry and thermooptical analysis were used to determine (crystal to mesomorphic (LC), and LC to isotropic) phase transition temperatures (Table 1, Fig. 1).